The Capability of Multi-Layer Material of A Pitched Roof in Reducing Noises - Setiyowati, Ernaning; Alfanani, Hanif; C. Nisa, Enita; Aisyah, Siti (International Journal of Engineering and Technology, 2026)
Noise is an annoying sound that should be avoided from entering a building. Therefore, A building should have a well-insulating material to prevent noises. The roof is one part of the building that should be covered by the material. One alternative way to build an insulating material is to compile the roof by some layered material. This research aims to discover a compatible tiered roof to be composed in a pitched roof to decrease noises from outside the building. The layered material applied in this research are wire, aluminum foil, white fiber met, and ijuk. This research is an experimental study using a model that was measured straight in the field using an SLM appliance. The result of this study indicates that the multi-layered pitched roof can decrease noises more than a general roof tile. It can lower noise by about 11 dB.
Keywords: layered pitched roof; room acoustic; noise; sound